Borderline Personality Pathology in an At Risk Mental State Sample - Paust, Tobias; Theodoridou, Anastasia; Müller, Mario; Wyss, Christine; Obermann, Caitriona; Rössler, Wulf; Heekeren, Karsten (Frontiers in Psychiatry, 2019)
Transient psychotic symptoms in patients with borderline personality disorder seem to be similar to those in patients with psychotic disorders. Especially in the field of early detection of psychosis, this might lead to individuals with borderline personality disorder being wrongly classified as subjects at risk for developing a manifest psychosis. The aim of the present study was to investigate the occurrence of borderline symptoms in a sample of subjects at risk for psychosis as well as possible effects on the transition rate. 70 help seeking individuals of an early psychosis recognition center were additionally examined for borderline symptoms by the borderline symptom checklist. We found a significant correlation between borderline symptomatology and positive symptoms assessed by the structured interview for prodromal symptoms. There were no associations between basic symptoms for psychosis and borderline symptoms. In addition, there was no influence of borderline symptomatology on the rate of transition into a manifest schizophrenic disease. In conclusion, borderline personality disorder should not be an exclusion criterion for the screening for psychosis or for an early intervention treatment. On the other hand, not every patient with borderline personality disorder, (especially those not suffering from hallucinations, unusual thought content or persecutory ideas) should automatically be screened for the risk of developing a psychotic disorder.